2018
DOI: 10.1002/art.40457
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study of the Validity and Reliability of Responses to Hand Cold Challenge as Measured by Laser Speckle Contrast Imaging and Thermography

Abstract: ObjectiveReliable and objective outcome measures to facilitate clinical trials of novel treatments for systemic sclerosis (SSc)–related Raynaud's phenomenon (RP) are badly needed. Laser speckle contrast imaging (LSCI) and thermography are noninvasive measures of perfusion that have shown excellent potential. This multicenter study was undertaken to determine the reliability and validity of a hand cold challenge protocol using LSCI, standard thermography, and low‐cost cell phone/mobile phone thermography (hence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 33 publications
0
72
0
5
Order By: Relevance
“…66 Recent evidence suggests that laser speckle contrast imaging is a highly reliable method to assess peripheral blood perfusion in patients with SSc and healthy controls. 66,67 Laser speckle flowmetry measures perfusion at a single point and requires further research including to examine the discriminatory capacity (e.g. between primary and secondary RP) of the technique.…”
Section: Laser-based Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…66 Recent evidence suggests that laser speckle contrast imaging is a highly reliable method to assess peripheral blood perfusion in patients with SSc and healthy controls. 66,67 Laser speckle flowmetry measures perfusion at a single point and requires further research including to examine the discriminatory capacity (e.g. between primary and secondary RP) of the technique.…”
Section: Laser-based Techniquesmentioning
confidence: 99%
“…However, the availability of relatively low-cost mobile phone-based thermographic imaging devices may facilitate wider access to infrared thermography used under ambient conditions. 67 In addition, there are significant differences in thermography imaging protocols between centres and internationally agreed protocols/consensus would help facilitate larger multi-centre studies of SSc-vasculopathy and potential future incorporation into routine clinical practice.…”
Section: Infrared Thermographymentioning
confidence: 99%
“…43 As baseline images were more helpful, a mobile phone thermography seems to be a feasible additional tool in the assessment of patients with RP. 44 The first multicenter study that was undertaken to determine the reliability and validity of a hand cold challenge protocol using mobile phone thermography in patients with SScrelated RP confirmed that small variations in room temperature are acceptable during the imaging. 44 Further research is needed to establish ranges of normality and abnormality and to validate the use of this method.…”
Section: Evaluation Of the Microcirculation Capillaroscopymentioning
confidence: 98%
“…44 The first multicenter study that was undertaken to determine the reliability and validity of a hand cold challenge protocol using mobile phone thermography in patients with SScrelated RP confirmed that small variations in room temperature are acceptable during the imaging. 44 Further research is needed to establish ranges of normality and abnormality and to validate the use of this method. 44 Laser Doppler and other techniques Laser Doppler techniques are tools for microcirculatory research evaluating peripheral blood flow.…”
Section: Evaluation Of the Microcirculation Capillaroscopymentioning
confidence: 98%
See 1 more Smart Citation